Budaya Religius dalam Membentuk Kepribadian Muslim Peserta Didik - Munif, Muhammad; Aisyah, Nur; Umami, Liza (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
Students need to be indoctrinated with the importance of having a decent Muslim personality. The Muslim personality is characterised by beliefs, attitudes, choices, and behaviours that are grounded in Islamic principles. As such, developing this personality requires more than simply education—it also requires modelling and habituation. Thus, the purpose of this research is to investigate and explain how Islamic culture shapes the Muslim personalities of MTsN 1 Probolinggo pupils. A qualitative descriptive methodology, akin to a case study, was used to collect the data. Data collection methods included documentation, observation, and interviews. Data reduction, display, and conclusion-drawing were used in the analytical process. The study's findings demonstrate that MTsN 1 Probolinggo implements religious culture in a number of ways, including communal prayer, Al-Qur'an coaching, infaq, tahlil, istighasah, and environmental care